The Effect of Ownership Structure on Firm Value with Investment Decision as Intervening Variable (Empirical Study of the Listed Companies in Indonesia Stock Exchange Period 2008-2014) - Indah Sulistyo; T Sutrisno; Nurkholis Nurkholis (Institute of Research and Community Service, University of Brawijaya)
This study aimed to examine the effect of ownership structure on firm value with investment decision as an intervening variable. The ownership structure proxied by managerial ownership structure and institutional ownership structure. The investment decision proxied by Market to Book Value of Assets. The firm value proxied by Price to Book Value. Population in this study are all companies listed on the Indonesian Stock Exchange (IDX) in the period 2008-2014. Selection of the sample in this study based on purposive sampling method. Based on these criteria there are 99 companies each year that requirements in the study. This study used multiple linear regression and path analysis. The results showed that managerial ownership and institutional ownership has no effect on investment decision, while the investment decision effect on firm value, managerial ownership has a negative effect on firm value, and institutional ownership has no effect on firm value. The investment decision is not a variable that mediates the relationship between the ownership structures with firm value. These findings reinforce previous research that reveals ownership concentration because there has not been a clear separation between ownership structure with the control of the company companies listed on the Indonesian Stock Exchange (IDX).Keywords: Managerial Ownership Structure, Institutional Ownership Structure, Investment Decision, and Firm Value